Public–private partnerships in practice: collaborating to improve health finance policy in Ghana and Kenya. Issue 7 (13th June 2018) - Suchman, Lauren; Hart, Elizabeth; Montagu, Dominic
Abstract: Social health insurance (SHI), one mechanism for achieving universal health coverage, has become increasingly important in low- and middle-income countries (LMICs) as they work to achieve this goal. Although small private providers supply a significant proportion of healthcare in LMICs, integrating these providers into SHI systems is often challenging. Public–private partnerships in health are one way to address these challenges, but we know little about how these collaborations work, how effectively, and why. Drawing on semi-structured interviews conducted with National Health Insurance (NHI) officials in Kenya and Ghana, as well as with staff from several international NGOs (INGOs) representing social franchise networks that are partnering to increase private provider accreditation into the NHIs, this article examines one example of public–private collaboration in practice. We found that interviewees initially had incomplete knowledge about the potential for cross-sector synergy, but both sides were motivated to work together around shared goals and the potential for mutual benefit. The public–private relationship then evolved over time through regular face-to-face interactions, reciprocal feedback, and iterative workplan development. This process led to a collegial relationship that also has given small private providers more voice in the health system. In order to sustain this relationship, we recommend that both public and private sector representatives develop formalized protocols for working together, as well as less formal open channels for communication. Models for aggregating small private providers and delivering them to government programmes as a package have potential to facilitate public–private partnerships as well, but there is little evidence on how these models work in LMICs thus far.